2018
DOI: 10.1080/21505594.2018.1504560
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Plasmodiophora brassicae effectors — A challenging goal

Abstract: Clubroot is an economically important disease affecting Brassica plants worldwide. Plasmodiophora brassicae is the protist pathogen associated with the disease, and its soil-borne obligate parasitic nature has impeded studies related to its biology and the mechanisms involved in its infection of the plant host. The identification of effector proteins is key to understanding how the pathogen manipulates the plant’s immune response and the genes involved in resistance. After more than 140 years studying clubroot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 84 publications
0
33
0
Order By: Relevance
“…), and we manually looked for cysteine residue number, RxLR motif, Pexel motif, and any functional motif present in the P. brassicae small secreted proteins as previously suggested (Pérez‐López et al. ). These proteins were further analyzed with ApoplastP (Sperschneider et al.…”
Section: Methodsmentioning
confidence: 99%
“…), and we manually looked for cysteine residue number, RxLR motif, Pexel motif, and any functional motif present in the P. brassicae small secreted proteins as previously suggested (Pérez‐López et al. ). These proteins were further analyzed with ApoplastP (Sperschneider et al.…”
Section: Methodsmentioning
confidence: 99%
“…Clubroot is caused by the obligate parasite Plasmodiophora brassicae Woronin and is recognized as a major devastating disease in Brassicaceae that poses an emerging threat to Brassica crop production [ 17 ]. Clubroot disease was first reported in Russia in 1878 by Woronin and rapidly expanded to other countries like Europe, Brazil, South Africa, Australia, New Zealand, and China [ 17 ]. The infection of plants by P. brassicae is a two-phase process ( Figure 1 ).…”
Section: Infection Process Of the Pathogensmentioning
confidence: 99%
“…This observation provides an additional clue in deciphering the arsenal of virulence mechanisms employed by L. maculans , one of the most notoriously adaptive disease-causing pathogens of the Brassica family. In Clubroot, small secreted proteins (SSPbPs) have been identified that were assumed to play critical functions in primary and secondary infections, leading to hypertrophic tissue development [ 177 , 178 ]. For bacterial pathogens, such as X. campestris and P. carotovorum , a variety of mechanisms are deployed to evade host resistance including the release of extracellular enzymes such as cellulase, mannanase, pectinase, protease, polygalacturonases (PGs) and pectate lyase (Type II secretion system), the injection of effector proteins (Type III secretion system), as well as the production of exopolysaccharides and biofilm formation [ 179 , 180 , 181 ].…”
Section: Application Of Omics Technologies In Brassica mentioning
confidence: 99%
“…The gene expression profile from the P. brassicae Pb3 genome assembly revealed that the pathogen contains genes that are associated with the biosynthesis of the plant hormones cytokinin and auxin, suggesting a potential role for these hormones in virulence activity in the host plant [ 203 ], while gene clusters for the synthesis of the ABA hormone were detected in L. maculans , suggesting a putative role of ABA production in disease progression in B. napus [ 204 ]. One of the well-characterised effectors for P. brassicae is the benzoic acid (BA)/SA methyltransferase protein ( PbBSMT ), which suppresses host SA signalling during plant defence [ 177 ]. The functional role of PbBSMT is similar to that of the SABATH methyltransferase gene family in A. thaliana , AtBSMT1 , where the genes play a role in converting SA into methyl salicylate (MeSA), which is the inactive form of SA, thereby compromising the SAR defence response [ 205 ].…”
Section: Application Of Omics Technologies In Brassica mentioning
confidence: 99%